Causal association of gut microbiota on spondyloarthritis and its subtypes: a Mendelian randomization analysis - Tang, Jun; Mo, Shiyan; Fan, Lina; Fu, Shihui; Liu, Xiaofei (Frontiers in Immunology, 2024)
Background: Despite establishing an association between gut microbiota and spondyloarthritis (SpA) subtypes, the causal relationship between them remains unclear.Methods: Gut microbiota data were obtained from the MiBioGen collaboration, and SpA genomewide association study (GWAS) summary data were obtained from the FinnGen collaboration. We conducted a two-sample Mendelian randomisation (MR) analysis using the inverse varianceweighted method supplemented with four additional MR methods (MR-Egger, weighted median, simple mode, and weighted mode). Pleiotropy and heterogeneity were also assessed. Reverse MR analysis was used to detect reverse causal relationships. This is a provisional file, not the final typeset article Results: We identified 23 causal links between specific gut microbiota taxa and SpA levels. Of these, 22 displayednominal causal associations and only one demonstrated a robust causal connection. Actinobacteria id.419 increased the risk of ankylosing spondylitis (AS)(odds ratio (OR) = 1.86, 95% confidence interval (CI): 1.29-2.69, P=8.63E-04). The family Rikenellaceae id.967 was associated with a reduced risk of both AS (OR = 0.66, 95% CI:0.47-0.93, P=1.81E-02) and psoriatic arthritis (OR = 0.70, 95% CI:0.50-0.97, P=3.00E-02). Bacillales id.1674 increased the risk of AS (OR = 1.23, 95% CI:1.00-1.51, P=4.94E-02) and decreased the risk of enteropathic arthritis (OR = 0.56, 95% CI:0.35-0.88, P=1.14E-02). Directional pleiotropy or heterogeneity was not observed. No reverse causal associations were observed between the diseases and gut microbiota.Our MR analysis suggested a genetic-level causal relationship between specific gut microbiota and SpA, providing insights into the underlying mechanisms behind SpA development, mediated by gut microbiota.